ANALISIS PENINGKATAN KUALITAS LAYANAN E-LEARNING PALCOMTECH MENGGUNAKAN PENDEKATAN WEBQUAL 4.0 DAN E-LEARNING MATURITY MODEL(EMM) - maria, Fitri; Herdiansyah, M. Izman; Sutabri, Tata; Kunang, Yesi Novaria (Jusikom : Jurnal Sistem Komputer Musirawas, 2024)
E-Learning is a very important learning method, especially in the context of course and training institutions (LKP) such as PalComTech. The study will be conducted to analyze the improvement of the quality of the LKP PalComTech e-learning system using the Webqual 4.0 approach. and E-learning Maturity Model (eMM). Thus the main objectives of this thesis are: Analyzing the Quality of e-Learning Services: Conducting an in-depth evaluation of various aspects of the quality of e-learning services provided by LKP PalComTech, including content, usability, interactivity, and reliability The abstract must be clear, descriptive and must provide a brief overview of the problem being studied. Applying the Webqual 4.0 approach to analyze the quality of e-learning services, thus providing a comprehensive understanding of the performance of the e-learning platform. Providing concrete recommendations for the improvement and development of the LKP PalComTech e-learning platform.